Non-invasive integrated sampling design to monitor the wolf population in Piemonte, Italian Alps - Marucco, Francesca; Avanzinelli, Elisa; BOITANI, Luigi (ASSOC TERIOLOGICA ITALIANA, 2012)
The natural return of the wolf (Canis lupus) in the western Alps of Italy and France at the beginning of the 1990's, after 70 years of absence, is an important ecological and social event. The Regione Piemonte, in the course of the Progetto Lupo Piemonte, intensively monitored the wolf population over the Piemonte territory from 1999 to 2010. We estimated four main population parameters over time (wolf population size, number of packs, distribution, and effective population size) in order to follow the natural recolonization process over the Alps. An integrated sampling approach was designed to collect data to estimate simultaneously and cost-effectively these four parameters. This combined monitoring program allowed the development of specific management strategies for the mitigation of wolf-human conflicts, given the protected status of the alpine wolf population. This transboundary wolf population, which dispersed over the Alps of Italy, France, Switzerland, and now is reaching the Eastern Alps, has been considered a unique and distinct entity by the European Commission after the "Guidelines for Population Level Management Plans for large Carnivores". Therefore, it should be monitored and managed as such over the boundaries, and this cost-effective sampling approach should be considered in this framework.